Improved tree routing protocol in zigbee networks - Al-Harbawi, Mostafa Kamil Abdulhusain (2010)
Wireless Sensor Networks (WSNs) is becoming more important in various application areas. Many application scenarios require connectivity between WSN’s nodes to transmit the collected data to a sink node. ZigBee is an industrial standard for wireless ad hoc networks based on IEEE 802.15.4. It has been developed for low cost, low data rate and low power consumption. In the ZigBee standard, network layer defines two routing protocols namely Ad Hoc On-demand Distance Vector (AODV) and Tree Routing (TR). TR protocol follows the tree topology (parent-child) in forwarding the data to the sink node, However, the source node cannot know if the sink is located nearby to the source node or if it is not in the sub-tree. In this case it will follow the tree topology which will use a lot of hops to arrive to the sink node. The objective of this thesis was to develop the TR protocol for ZigBee network and is called Improved Tree Routing (ImpTR) protocol which is computationally simple in finding the shortest path to transmit data packets to the sink node, and does not need any addition in hardware. ImpTR protocol uses an approach to select next hope depending on new algorithm and uses the same tree topology construction for distributing address to all sensor nodes in the network. ImpTR determines the best path to the sink node depending on the tables of the neighbouring nodes, which is part of the existing ZigBee network specification. Packets are forwarded to neighbour node if the path to the sink through neighbour node is shorter than the path through personal area network (PAN) coordinator. The unreliability and inefficiency of the TR originates from the limited links for routes, i.e., parent-child links. If any ZigBee router loses its link to its parent the routing path is broken and the TR cannot recover the routing path by itself , for that the second main objective is overcome the link failure problem. ImpTR algorithm reduces the average end-to-end delay by (10-31) % which is the time needs to transmit packets between source and sink node, decrease the energy consumption from the whole network by (8-40) % , reduce the number of hops need to transmit data packets to sink node by (3-32)%, and increases the average throughput by (4-65) % which is average number of bits receive in sink node per second.